Wadah Pembelajaran Masyarakat pada Zawiyyah Sirr el-Sa’adah Sidamulya oleh Muqoddam Tijaniyah - Salma Mumtazah; Tendi Tendi; Izzudin Izzudin; Lukman Zen; Nurkholidah Nurkholidah (UIN Sunan Gunung Djati Bandung, 2023)
This research aims to discuss the community learning container at Zawiyyah Sirr el-Sa'adah Sidamulya by Muqoddam Tijaniyah. This research uses qualitative descriptive method. The results and discussion of this study indicate that the driving teacher has an important and valuable role as a problem solver in society even though it is still limited to the Zawiyah Sirr el-Sa'adah Sidamulya Astanajapura Cirebon community. The learning carried out by the driving teacher, Kang Naqib, is about basic Islamic education, economic empowerment, and an attitude of life full of total surrender to fate. This research concludes that community-based education is a learning platform that prioritizes fundamental issues in society, as played by Muqoddam Tijaniyah in the Zawiyah Sirr el-Sa'adah Sidamulya Astanajapura Cirebon community.